Body cavity cells of Parachela during their active life. (December 2016) - Hyra, Marta; Rost‐Roszkowska, Magdalena M.; Student, Sebastian; Włodarczyk, Agnieszka; Deperas, Marcin; Janelt, Kamil; Poprawa, Izabela
Abstract : The body cavity cells (storage cells, storage bodies) of four species of Parachela (hermaphroditic Isohypsibius granulifer granulifer, parthenogenetic Hypsibius dujardini, gonochoristic Xerobiotus pseudohufelandi, gonochoristic Macrobiotus polonicus ) were analysed during their active life using light, confocal (laser scanning), and scanning and transmission electron microscopy. The ultrastructure of the storage cells confirmed previous studies suggesting a high level of metabolic activity. Additionally, we revealed the participation of the storage cells of H. dujardini, I. g. granulifer, and M. polonicus in the synthesis of vitellogenins. This did not seem to apply for X. pseudohufelandi . All of the species that were examined in this study accumulated polysaccharides, proteins, and lipids in their body cavity cells, but the amount of these components differed in each species. Isohypsibius g. granulifer accumulated a huge amount of polysaccharides and smaller amounts of lipids and proteins, H. dujardini and M. polonicus primarily accumulated lipids and small amounts of polysaccharides and proteins, whereas X. pseudohufelandi primarily accumulated polysaccharides and lipids, and a small amount of proteins.